Application of Cyclohexane‐1, 3‐diones in the Synthesis of Six‐Membered Nitrogen‐Containing Heterocycles. Issue 12 (23rd March 2022) - Sharma, Dharminder; Kumar, Manish; Kumar, Sandeep; Basu, Amartya; Bhattacherjee, Dhananjay; Chaudhary, Abha; Das, Pralay
Abstract: Cyclohexane‐1, 3‐dione and its derivatives are imperative precursors in synthetic organic chemistry as they are useful intermediates for the synthesis of a wide range of biologically active natural products, heterocycles and pharmaceuticals. Recently, cyclohexane‐1, 3‐diones have been used for the synthesis of varied array of six‐membered nitrogen‐containing heterocycles in the presence of aldehydes, acetoacetic esters, malononitrile, chalcones, coumarins, acetophenones, amino acids, amines, etc. under catalytic and non‐catalytic conditions. Newest studies on the importance of these heterocycles motivated us to compile all the recently developed processes which include the fabrication of six‐membered nitrogen heterocycles. This article is mainly focused on the efficient synthesis of six‐membered N ‐heterocycles i. e. 1, 4‐dihydropyridine, acridine‐1, 8‐diones, benzoacridinones, quinolones and pyridine derivatives from cyclohexane‐1, 3‐diones as one of the substrates, published for the last ten years. Abstract : This article summarizes the potential of cyclohexane‐1, 3‐dione and its derivatives for the synthesis of a number of biologically active heterocycles and natural products. The applications towards six‐membered N ‐heterocycles using different catalytic methods, energy sources and reaction medium has been discussed for the synthesis of valuable polyhydroquinoline, benzoacridinones, quinolones, acridine‐1, 8‐diones and pyridine derivatives.